Influence of presence of the coach on the behaviour of the athlete in training. Issue 15 (10th November 2011) - Pinto, D; Gomes, H; Santos, L; Cruz, C; Marques, A
Abstract : In sport, the skills development of the athletes results from the influence of many factors, such as, the role of the coach, training mode, physical recovery, support from parents and family and the pleasure of the practice. The coach has the main responsibility in achieving of the high level of performance of the athlete; he is responsible for structuring the training and competition of athletes in order to ensure the objectives. The aim of this study was to assess if there are differences in the behaviour of the swimmers during the course of a training task, in the presence and in the absence of the coach while performing the task. Twelve male swimmers, aged between 9 and 11 years, with a training period of about 5 years and practicing 4/5 times/week participated in the study. It was observed 3 training sessions where we obtained 6 series. To compare the performance on the task, compliments of break-times, and the occurrence of deviant behaviours, we use non-parametric Wilcoxon test and X 2 . The athletes' performance in accomplishing the task prescribed by the coach is better when the coach is present (Z= −2.589, p = <0.01). When the coach was present, 90% of the swimmers completed the break-times, contrasting with the 10% who did it in the absence of him ( X 2 (1) = 76.349, p>0.001). This study showed no significant differences in the occurrence of deviant behaviours in both observed situations (0.8% vs 5.8%; X 2 (1) = 3.233, p>0.05). The results suggest that in low ages, the presence of the coach is an important factor for accuracy in compliment of tasks by the athletes and induces the quality of training and the high level of performance. However, the presence of the coach seems not have influence in the occurrence of deviant behaviour.